Total Quality Management and Operational Performance - S. Saharuddin; Putra Syarif; R. Ramlawati; A. Anis (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study examines the effect of Total Quality Management (TQM) practices on operational performance at PT So Good Food. The study employed a quantitative survey design involving 30 employees selected through purposive sampling. The respondents were employees who had worked at the company for at least one year and were considered to have sufficient experience and understanding of the company’s quality-management practices and operational processes. TQM was represented by customer satisfaction, employee empowerment, continuous quality improvement, and fact-based management, while operational performance served as the dependent variable. Data were collected using a structured questionnaire with a five-point Likert scale and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, partial t-tests, and a simultaneous F-test. The findings indicate that the TQM dimensions simultaneously have a significant effect on operational performance. Partially, employee empowerment, continuous quality improvement, and fact-based management have positive and significant effects on operational performance, whereas customer satisfaction does not have a significant partial effect. These findings suggest that internal quality-management practices, particularly employee involvement, continuous process improvement, and data-based decision-making, play an important role in supporting operational effectiveness. The study is limited to a small sample from a single organization; therefore, the findings should be interpreted and generalized cautiously.